THE ROLE OF “DETECTIVE DOCTORS” IN EXPOSING THE SKINCARE MAFIA: HEALTH COMMUNICATION TO RAISE PUBLIC AWARENESS - Talitha Carlen Anora Junus (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The beauty and skincare industry in Indonesia is growing rapidly and promising. However, behind this growth, there has been a revelation of numerous ingredients in skincare products that do not match their claims, with many containing harmful substances such as mercury, hydroquinone, and more. This issue began to surface when a beauty doctor, often referred to as the "Detective Doctor," examined and exposed skincare products suspected of being unregistered and containing dangerous ingredients. This research aims to analyze the role of health communication in raising public awareness about the skincare mafia practices through the role of the "Detective Doctor." The method used is qualitative descriptive analysis with case studies of several campaigns conducted by the "Detective Doctor" on social media and other public channels. The results show that the "Detective Doctor" not only reveals dangerous skincare products through scientific research but also plays a role in delivering information to the public via accessible communication platforms such as social media and podcasts. This campaign successfully increased public awareness of the importance of choosing safe beauty products, as well as the importance of verifying skincare product ingredients. This research highlights the significant role of health communication in combating illegal practices in the beauty industry and demonstrates how the "Detective Doctor" can be an agent of change in public health education.